2021
DOI: 10.1016/j.jbc.2021.100945
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically disordered electronegative clusters improve stability and binding specificity of RNA-binding proteins

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…Indeed, the negatively charged Nephrin intracellular domain forms phase-separated nuclear bodies 55 . Other studies also indicated that “hyperacidic” sequences are utilized as interacting domains or interaction regulators for various proteins 45 , 46 , 56 – 59 . In addition, essential yeast proteins, such as the RNA binding protein Nab3p 60 , 61 , the transcription elongation regulator Spt5p 62 , 63 , and the 40S subunit biogenesis protein Kri1p 64 , 65 , contain 23, 19, and 15 D/E runs from the 114th, 148th, and 52nd residues within the 802, 1063, and 591 aa length polypeptides, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the negatively charged Nephrin intracellular domain forms phase-separated nuclear bodies 55 . Other studies also indicated that “hyperacidic” sequences are utilized as interacting domains or interaction regulators for various proteins 45 , 46 , 56 – 59 . In addition, essential yeast proteins, such as the RNA binding protein Nab3p 60 , 61 , the transcription elongation regulator Spt5p 62 , 63 , and the 40S subunit biogenesis protein Kri1p 64 , 65 , contain 23, 19, and 15 D/E runs from the 114th, 148th, and 52nd residues within the 802, 1063, and 591 aa length polypeptides, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The inter-domain flexibility may also be present in other SR proteins with tandem RRMs, such as SRSF4, SRSF5, SRSF6, and SRSF9, whose tandem-RRM linkers range from 22 to 38 amino acids. A more advanced method called RNA Bind-n-Seq (RBNS) has been developed and successfully applied to several RNA-binding proteins in profiling the landscape of RNA-binding specificity. , However, this method assumes that the length of cognate RNA motifs is a constant, which is not applicable for RNA binding with SRSF1 and other SR proteins with tandem RRMs. Therefore, new methods with improved procedures and/or algorithms are needed to determine the RNA-binding specificity of SR proteins with tandem RRMs.…”
Section: Discussionmentioning
confidence: 99%
“…The substantial impact of the L270R mutation on editing without an overall impact on CC structure suggests that it may have affected protein or RNA interactions and/or conformations within the CCs which are critical for editing. This implies that the other IDRs in A3 also have important functions in editing, perhaps by interacting with proteins or with RNA as suggested by the characteristics of these protein sequences which have been shown in other proteins to facilitate interactions with RNA (Zaharias et al 2021;Zeke et al 2022;Luo et al 2023). The IDRs may provide the CCs with flexibility to accommodate many diverse substrate sequences and conformational changes during editing, like what has been shown for mammalian LIN28A (Nam et al 2011;Wang et al 2017).…”
Section: Ccsmentioning
confidence: 96%
“…Alternatively, the OB-folds might work together to resolve secondary structures in the mRNA as has been previously suggested (Voigt et al 2018). The editing substrate may also interact with other domains of A3 including its ZFs and IDRs both of which have been implicated in RNA binding in other systems (Tompa and Csermely 2004;Dyson 2012;Corley et al 2020;Zaharias et al 2021;Luo et al 2023). Overall, the data suggest that during editing the substrate RNA interacts with A3 via base stacking and charged interactions within the OB-fold, and by interaction with certain residues within the IDRs and with the ZFs.…”
Section: Rna Interactions and Effects On Editingmentioning
confidence: 99%